Beware the wolfman - William, Kate.; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1994)
On assignment for a newpaper in London, Elizabeth and Jessica Wakefield hunt a savage werewolf. When he ransacks their room and leaves telltale claw marks, the twins know they must capture the maniac before he captures -- and kills -- them. Terrified, they follow the villain's trail, unsuspecting that it's part of his deadly plot to lead them straight into his lair. Armed with anti-werewolf potions and amulets, can the twins protect themselves when the moon is full, or are they destined to die in London?
Keywords: Werewolves -- Juvenile fiction; English fiction; United States; Young adult fiction